Increased circulating microRNA-122 is a biomarker for discrimination and risk stratification in patients defined by sepsis-3 criteria - Rahmel, Tim (PLoS One, 2018)
BACKGROUND: Sepsis is now operationally defined as life-threatening organ dysfunction caused by an infection, identified by an acute change in SOFA-Score of at least two points, including clinical chemistry such as creatinine or bilirubin concentrations. However, little knowledge exists about organ-specific microRNAs as potentially new biomarkers. Accordingly, we tested the hypotheses that micro-RNA-122, the foremost liver-related micro-RNA (miR), 1) discriminates between sepsis and infection, 2) is an early predictor for mortality, and 3) improves the prognostic value of the SOFA-score. METHODS: We analyzed 108 patients with sepsis (infection + increase SOFA-Score ≥2) within the first 24h of ICU admission and as controls 20 patients with infections without sepsis (infection + SOFA-Score ≤1). Total circulating miR was isolated from serum and relative miR-122 expression was measured (using spiked-in cel-miR-54) and associated with 30-day survival. RESULTS: 30-day survival of the sepsis patients was 63%. miR-122 expression was 40-fold higher in non-survivors (p = 0.001) and increased almost 6-fold in survivors (p = 0.013) compared to controls. miR-122 serum-expression discriminated both between sepsis vs. infection (AUC 0.760, sensitivity 58.3%, specificity 95%) and survivors vs. non-survivors (AUC 0.728, sensitivity 42.5%, specificity 94%). Multivariate Cox-regression analysis revealed miR-122 (HR 4.3; 95%-CI 2.0–8.9, p<0.001) as independent prognostic factor for 30-day mortality. Furthermore, the predictive value for 30-day mortality of the SOFA-Score (AUC 0.668) was improved by adding miR-122 (AUC 0.743; net reclassification improvement 0.37, p<0.001; integrated discrimination improvement 0.07, p = 0.007). CONCLUSIONS: Increased miR-122 serum concentration supports the discrimination between infection and sepsis, is an early and independent risk factor for 30-day mortality, and improves the prognostic value of the SOFA-Score, suggesting a potential role for miR-122 in sepsis-related prediction models.